2012
DOI: 10.1016/j.ccr.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell HIF-1α and HIF-2α Differentially Regulate Metastatic Success

Abstract: SummaryThe hypoxia inducible transcription factors (HIFs) control many mediators of vascular response, including both angiogenic factors and small molecules such as nitric oxide (NO). In studying how endothelial HIF response itself affects metastasis, we found that loss of HIF-1α in endothelial cells reduces NO synthesis, retards tumor cell migration through endothelial layers, and restricts tumor cell metastasis, and that loss of HIF-2α has in each case the opposite effect. This results from differential regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 61 publications
5
141
0
1
Order By: Relevance
“…Primary lung endothelial cell isolation. Primary endothelial cells were isolated and cultured from lungs of L1cre-HIF2α and WT mice, as previously described (25). Detailed methods are given in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Primary lung endothelial cell isolation. Primary endothelial cells were isolated and cultured from lungs of L1cre-HIF2α and WT mice, as previously described (25). Detailed methods are given in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…For example, HIF-1a promotes cell cycle arrest, whereas HIF-2a promotes progression through the cell cycle, likely in a cell context-dependent manner (Keith et al 2012). In murine macrophages, keratinocytes, and endothelial cells, Hif-1a promotes NO production through activation of the inducible NO synthase (Nos2) gene, whereas Hif-2a inhibits NO production through the induction of the arginase (Arg) gene Branco-Price et al 2012;Cowburn et al 2013). Finally, Hif1a +/À mice display blunted respiratory responses to chronic hypoxia, while Hif2a +/À mice display exaggerated carotid body sensitivity to hypoxia ( Fig.…”
Section: The Hif Pathwaymentioning
confidence: 99%
“…However, despite the extensive homology it shares with HIF-1a, HIF-2a has its own physiological functions through induction of its unique target genes such as erythropoietin, octamer-binding transcription factor 4, and deltalike ligand 4 (18). Furthermore, studies of HIF-1a and HIF-2a in solid tumors have revealed their opposing roles in cell growth, energy metabolism, NO homeostasis, and other cell functions (18,19). These findings led us to test whether HIF-2a has functions that are distinct from those of HIF-1a in obese adipose tissue even though both HIF-1a and HIF-2a might be involved in angiogenesis in response to adipose tissue hypoxia.…”
mentioning
confidence: 99%